Women and development-forced evictions: realities, responses and solidarity. Issue 8 (17th November 2019) - Bedi, Heather P.; Levitt Cea, Joanna
ABSTRACT: The loss of land, livelihoods and home associated with displacement frequently has profound impacts on people, with women particularly vulnerable to violence, impoverishment and marginalisation. Lessons gleaned broadly from the gendered experiences of displacement offer insights to those evicted and dispossessed for development projects. This article takes a gender lens to highlight activism related to development-forced evictions locally and globally, including efforts to demand state and corporate accountability. It concludes with insights on how applied research and solidarity across boundaries can help support, rather than undermine, women's leadership on these pressing issues.